The State of Resilience: A Leadership Forum and Community Workshop: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Over the past decade, resilience has gained significant traction across the nation and innovative programs are showing exciting progress in building resilient communities. For communities to be prepared for future extreme weather and climate events, as well as the chronic daily stressors, the momentum of implementing and taking action to build community resilience should continue to be fostered and expanded.
Keywords: Conflict and Security Issues

Countering the Threat of Improvised Explosive Devices: Basic Research Opportunities: Abbreviated Version - National Research Council (The National Academies Press, 2007)
Attacks in London, Madrid, Bali, Oklahoma City and other places indicate that improvised explosive devices (IEDs) are among the weapons of choice of terrorists throughout the world. Scientists and engineers have developed various technologies that have been used to counter individual IED attacks, but events in Iraq and elsewhere indicate that the effectiveness of IEDs as weapons of asymmetric warfare remains. The Office of Naval Research has asked The National Research Council to examine the current state of knowledge and practice in the prevention, detection, and mitigation of the effects of IEDs and make recommendations for avenues of research toward the goal of making these devices an ineffective tool of asymmetric warfare. The book includes recommendations such as identifying the most important and most vulnerable elements in the chain of events leading up to an IED attack, determining how resources can be controlled in order to prevent the construction of IEDs, new analytical methods and data modeling to predict the ever-changing behavior of insurgents/terrorists, a deeper understanding of social divisions in societies, enhanced capabilities for persistent surveillance, and improved IED detection capabilities.
Keywords: Conflict and Security Issues

University Research Centers of Excellence for Homeland Security: A Summary Report of a Workshop - National Research Council (The National Academies Press, 2004)
In establishing the Department of Homeland Security (DHS), the Administration and Congress determined that science and technology should play a key role in the nation’s efforts to counter terrorism. Congress included an S&T directorate prominently in the DHS. Within that directorate, is the Office of University Programs, which is responsible for sponsoring a number of homeland security centers of excellence in the nation’s universities. These centers are to work on a spectrum of short- and long-range R&D and carry out crosscutting, multidisciplinary work on a variety of threats. To assist it in planning for these centers, TSA asked the NRC to hold a workshop to generate a broad range of ideas to draw on to help define the centers. This report presents the results of that workshop including the major ideas that emerged from the discussions.
Keywords: Conflict and Security Issues

Workforce Development and Intelligence Analysis for National Security Purposes: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Beginning in October 2017, the National Academies of Sciences, Engineering, and Medicine organized a set of workshops designed to gather information for the Decadal Survey of Social and Behavioral Sciences for Applications to National Security. The fifth workshop focused on workforce development and intelligence analysis, and this publication summarizes the presentations and discussions from this workshop.
Keywords: Conflict and Security Issues

New Research Directions for the National Geospatial-Intelligence Agency: Workshop Report - National Research Council (The National Academies Press, 2010)
The National Geospatial-Intelligence Agency (NGA) within the Department of Defense has the primary mission of providing timely, relevant, and accurate imagery, imagery intelligence, and geospatial information--collectively known as geospatial intelligence (GEOINT)--in support of national security. In support of its mission, NGA sponsors research that builds the scientific foundation for geospatial intelligence and that reinforces the academic base, thus training the next generation of NGA analysts while developing new approaches to analytical problems. Historically, NGA has supported research in five core areas: (1) photogrammetry and geomatics, (2) remote sensing and imagery science, (3) geodesy and geophysics, (4) cartographic science, and (5) geographic information systems (GIS) and geospatial analysis.
Keywords: Conflict and Security Issues

Understanding Narratives for National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Beginning in October 2017, the National Academies of Sciences, Engineering, and Medicine organized a set of workshops designed to gather information for the Decadal Survey of Social and Behavioral Sciences for Applications to National Security. The sixth workshop focused on understanding narratives for national security purposes, and this publication summarizes the presentations and discussions from this workshop.
Keywords: Conflict and Security Issues

BioWatch and Public Health Surveillance: Evaluating Systems for the Early Detection of Biological Threats: Abbreviated Version - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Following the attacks of September 11, 2001 and the anthrax letters, the ability to detect biological threats as quickly as possible became a top priority. In 2003 the Department of Homeland Security (DHS) introduced the BioWatch program—a federal monitoring system intended to speed detection of specific biological agents that could be released in aerosolized form during a biological attack.
Keywords: Conflict and Security Issues

Testing of Defense Systems in an Evolutionary Acquisition Environment - National Research Council (The National Academies Press, 2006)
The Department of Defense (DoD) recently adopted evolutionary acquisition, a dynamic strategy for the development and acquisition of its defense systems. Evolutionary defense systems are planned, in advance, to be developed through several stages in a single procurement program. Each stage is planned to produce a viable system which could be fielded. The system requirements for each stage of development may be specified in advance of a given stage or may be decided at the outset of that stage's development. Due to the different stages that comprise an evolutionary system, there exists a need for careful reexamination of current testing and evaluation policies and processes, which were designed for single-stage developments.
Keywords: Conflict and Security Issues

Avoiding Technology Surprise for Tomorrow's Warfighter: Symposium 2010 - National Research Council (The National Academies Press, 2010)
The Symposium on Avoiding Technology Surprise for Tomorrow's Warfighter is a forum for consumers and producers of scientific and technical intelligence to exchange perspectives on the potential sources of emerging or disruptive technologies and behaviors, with the goal of improving the Department of Defense's technological warning capability. This volume summarizes the key themes identified in the second and most recent symposium, a two-day event held in Suffolk, Virginia, on April 28 and 29, 2010. The symposium combined presentations highlighting cutting-edge technology topics with facilitated discourse among all participants. Three categories of surprise were identified: breakthroughs in product and process technology, new uses of existing technology, and the unexpectedly rapid progression of a technology to operational use. The incorporation of an adversary's own culture, history, beliefs, and value systems into analyses also emerged in discussions as an important factor in reducing surprise.
Keywords: Conflict and Security Issues

Making the Nation Safer: The Role of Science and Technology in Countering Terrorism - National Research Council (The National Academies Press, 2002)
Vulnerabilities abound in U.S. society. The openness and efficiency of our key infrastructures — transportation, information and telecommunications systems, health systems, the electric power grid, emergency response units, food and water supplies, and others — make them susceptible to terrorist attacks. Making the Nation Safer discusses technical approaches to mitigating these vulnerabilities. A broad range of topics are covered in this book, including:
Keywords: Conflict and Security Issues

Resilience for Compounding and Cascading Events - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
A cascading hazard refers to a primary event, such as heavy rainfall, seismic activity, or rapid snowmelt, followed by a chain of consequences that may range from modest (lesser than the original event) to substantial. Also, the type of cascading damage and losses may be more severe than if they had occurred separately. Currently, research on disasters has focused largely on those triggered by natural hazards interacting with vulnerable human systems (e.g., populations and organizations) and the built environment. Compounding and cascading natural hazards, whether acute or chronic in nature, can be further amplified by other events, such as public health outbreaks, supply chain disruptions and cyberattacks. Resilience for Compounding and Cascading Events explores strategies that would enable the nation to be better prepared for and respond to these disasters so that affected communities can not only rebuild, but do so in a manner that increases their resilience to future events.
Keywords: Conflict and Security Issues

Review Criteria for Successful Treatment of Hydrolysate at the Pueblo Chemical Agent Destruction Pilot Plant - National Research Council (The National Academies Press, 2015)
One of the last two sites with chemical munitions and chemical materiel is the Pueblo Chemical Depot in Pueblo, Colorado. The stockpile at this location consists of about 800,000 projectiles and mortars, all of which are filled with the chemical agent mustard. Under the direction of the Assembled Chemical Weapons Alternative Program (ACWA), the Army has constructed the Pueblo Chemical Agent Destruction Pilot Plant (PCAPP) to destroy these munitions. The primary technology to be used to destroy the mustard agent at PCAPP is hydrolysis, resulting in a secondary waste stream referred to as hydrolysate. PCAPP features a process that will be used to treat the hydrolysate and the thiodiglycol - a breakdown product of mustard - contained within. The process is a biotreatment technology that uses what are known as immobilized cell bioreactors. After biodegradation, the effluent flows to a brine reduction system, producing a solidified filter cake that is intended to be sent offsite to a permitted hazardous waste disposal facility. Water recovered from the brine reduction system is intended to be recycled back through the plant, thereby reducing the amount of water that is withdrawn from groundwater. Although biotreatment of toxic chemicals, brine reduction, and water recovery are established technologies, never before have these technologies been combined to treat mustard hydrolysate. At the request of the U.S. Army, Review Criteria for Successful Treatment of Hydrolysate at the Pueblo Chemical Agent Destruction Pilot Plant reviews the criteria for successfully treating the hydrolysate. This report provides information on the composition of the hydrolysate and describes the PCAPP processes for treating it; discusses stakeholder concerns; reviews regulatory considerations at the federal, state, and local levels; discusses Department of Transportation regulations and identifies risks associated with the offsite shipment of hydrolysate; establishes criteria for successfully treating the hydrolysate and identifies systemization data that should factor into the criteria and decision process for offsite transport and disposal of the hydrolysate; and discusses failure risks and contingency options as well as the downstream impacts of a decision to ship hydrolysate offsite.
Keywords: Conflict and Security Issues

Roots and Trajectories of Violent Extremism and Terrorism: A Cooperative Program of the U.S. National Academy of Sciences and the Russian Academy of Sciences (1995-2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
During the past 25 years, the U.S. National Academies of Sciences, Engineering, and Medicine, in collaboration with the Russian Academy of Sciences, have carried out a wide variety of activities to improve understanding of the challenges in containing and reducing ethnic conflicts, violent extremism, and terrorism. Roots and Trajectories of Violent Extremism and Terrorism provides an overview of this cross-ocean program, which has involved American and Russian scientists, engineers, and medical professionals from a large number of government agencies, leading research institutions, think tanks, educational institutions, analytical centers, and consulting and commercial firms in the two countries. This report highlights challenges addressed by the academies over many years that remain of current interest as the U.S., Russian, and other governments continue to cope with old and new forms of aggression that threaten the livelihood of populations at home and abroad.
Keywords: Conflict and Security Issues

Preparing for Terrorism: Tools for Evaluating the Metropolitan Medical Response System Program - Institute of Medicine (The National Academies Press, 2002)
The Metropolitan Medical Response System (MMRS) program of the U. S. Department of Health and Human Services (DHHS) provides funds to major U. S. cities to help them develop plans for coping with the health and medical consequences of a terrorist attack with chemical, biological, or radiological (CBR) agents. DHHS asked the Institute of Medicine (IOM) to assist in assessing the effectiveness of the MMRS program by developing appropriate evaluation methods, tools, and processes to assess both its own management of the program and local preparedness in the cities that have participated in the program. This book provides the managers of the MMRS program and others concerned about local capabilities to cope with CBR terrorism with three evaluation tools and a three-part assessment method. The tools are a questionnaire survey eliciting feedback about the management of the MMRS program, a table of preparedness indicators for 23 essential response capabilities, and a set of three scenarios and related questions for group discussion. The assessment method described integrates document inspection, a site visit by a team of expert peer reviewers, and observations at community exercises and drills.
Keywords: Conflict and Security Issues

Countering Urban Terrorism in Russia and the United States: Proceedings of a Workshop - National Research Council (The National Academies Press, 2006)
In January-February 2005, the National Academies Committee on Counterterrorism Challenges for Russia and the United States and the Russian Academy of Sciences Standing Committee on Counterterrorism held a workshop on urban terrorism in Washington, D.C. Prior to the workshop, three working groups convened to focus on the topics of energy systems vulnerabilities, transportation systems vulnerabilities, and cyberterrorism issues. The working groups met with local experts and first responders, prepared reports, and presented their findings at the workshop. Other workshop papers focused on various organizations' integrated response to acts of urban terrorism, recent acts of terrorism, radiological terrorism, biological terrorism, cyberterrorism, and the roots of terrorism.
Keywords: Conflict and Security Issues

Adapting to Shorter Time Cycles in the United States Air Force: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Air Force Studies Board of the National Academies of Sciences, Engineering, and Medicine hosted a three-part workshop series to investigate the changing paradigm of time and knowledge in modern-day warfare. Sponsored by the U.S. Department of Defense, three 2-day workshops were held virtually on September 16-17, 2020, September 23-24, 2020, and October 1-2, 2020. The objective of the first workshop was to explore the ways in which the U.S. Air Force (USAF) has adjusted its capabilities in response to past shifts in operational timing. In consideration of these past shifts, the second workshop aimed to consider when there could be an advantage to synchronize or desynchronize rates of change with adversaries. Participants had the opportunity to discuss lessons learned and possible changes for USAF Doctrine and future operations. The goal of the third workshop was to examine the implications to doctrine, concepts of operations, and command and control from the recent acceleration of battlespace operations, arising from wide-scale digitization, large-scale sensing, and faster technologies. In all three workshops, speakers explored the broader issues surrounding changing environments, and participants discussed ways to adapt to fundamental changes in the time constants of conflict. This proceedings is a factual summary of what occurred during the workshop series.
Keywords: Conflict and Security Issues

U.S. Air Force Strategic Deterrence Analytic Capabilities: An Assessment of Tools, Methods, and Approaches for the 21st Century Security Environment - National Research Council (The National Academies Press, 2014)
Since the early 1960s, the U.S. strategic nuclear posture has been composed of a triad of nuclear-certified long-range bombers, intercontinental ballistic missiles, and submarine-launched ballistic missiles. Since the early 1970s, U.S. nuclear forces have been subject to strategic arms control agreements. The large numbers and diversified nature of the U.S. nonstrategic (tactical) nuclear forces, which cannot be ignored as part of the overall nuclear deterrent, have decreased substantially since the Cold War. While there is domestic consensus today on the need to maintain an effective deterrent, there is no consensus on precisely what that requires, especially in a changing geopolitical environment and with continued reductions in nuclear arms. This places a premium on having the best possible analytic tools, methods, and approaches for understanding how nuclear deterrence and assurance work, how they might fail, and how failure can be averted by U.S. nuclear forces. U.S. Air Force Strategic Deterrence Analytic Capabilities identifies the broad analytic issues and factors that must be considered in seeking nuclear deterrence of adversaries and assurance of allies in the 21st century. This report describes and assesses tools, methods - including behavioral science-based methods - and approaches for improving the understanding of how nuclear deterrence and assurance work or may fail in the 21st century and the extent to which such failures might be averted or mitigated by the proper choice of nuclear systems, technological capabilities, postures, and concepts of operation of American nuclear forces. The report recommends criteria and a framework for validating the tools, methods, and approaches and for identifying those most promising for Air Force usage.
Keywords: Conflict and Security Issues

India-United States Cooperation on Global Security: Summary of a Workshop on Technical Aspects of Civilian Nuclear Materials Security - National Academy of Sciences (The National Academies Press, 2013)
The U.S. government has made safeguarding of weapons-grade plutonium and highly enriched uranium an international policy priority, and convened The 2010 Nuclear Security Summit in Washington, D.C., on April 12 and 13, 2010. Forty six governments sent delegations to the summit and twenty nine of them made national commitments to support nuclear security. During the Summit, India announced its commitment to establish a Global Centre for Nuclear Energy Partnership. The Centre is to be open to international participation through academic0 exchanges, training, and research and development efforts. India-United States Cooperation on Global Security is the summary of a workshop held by the U.S. National Academy of Sciences (NAS) together with its partner of more than 15 years, the National Institute for Advanced Studies (NIAS) in Bangalore, India. The workshop identified and examined potential areas for substantive scientific and technical cooperation between the two countries on issues related to nuclear material security. Technical experts from India and the United States focused on topics of nuclear material security and promising opportunities for India and the United States to learn from each other and cooperate. This report discusses nuclear materials management issues such as nuclear materials accounting, cyber security, physical security, and nuclear forensics.
Keywords: Conflict and Security Issues

Alternatives for the Demilitarization of Conventional Munitions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. military has a stockpile of approximately 400,000 tons of excess, obsolete, or unserviceable munitions. About 60,000 tons are added to the stockpile each year. Munitions include projectiles, bombs, rockets, landmines, and missiles. Open burning/open detonation (OB/OD) of these munitions has been a common disposal practice for decades, although it has decreased significantly since 2011.
Keywords: Conflict and Security Issues

2017-2018 Assessment of the Army Research Laboratory: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The National Academies of Sciences, Engineering, and Medicine's Army Research Laboratory Technical Assessment Board (ARLTAB) provides biennial assessments of the scientific and technical quality of the research, development, and analysis programs at the Army Research Laboratory (ARL), focusing on ballistics sciences, human sciences, information sciences, materials sciences, and mechanical sciences. This interim report summarizes the findings of the ARLTAB for the first year of this biennial assessment; the current report addresses approximately half the portfolio for each campaign; the remainder will be assessed in 2018.
Keywords: Conflict and Security Issues